Health effects of plants, light, and natural elements of biophilic interventions in confined settings: a systematic review - Zandi, Abdolrahim; Wung, Shu-Fen (Frontiers in Physiology, 2025)
Biophilic intervention strategies that incorporate plants, light, and organic elements are increasingly recognized for supporting well-being in confined environments. This systematic review analyzes health outcomes associated with edible greens and biophilic elements across 124 studies drawn from PubMed and Scopus, following PRISMA guidelines. The evidence demonstrates that greenery in confined settings—such as hospitals, eldercare, and space habitats—reduces stress, improves mood, and accelerates recovery, consistent with Stress Reduction Theory (SRT) and Attention Restoration Theory (ART). In space analogs, plant-based modules support cognitive function and improve habitat experience by producing food and oxygen. Despite these benefits, a few challenges remain: infection control, spatial constraints, and operational limitations can hinder adoption. Nonetheless, tailored biophilic systems represent a promising path to enhance health and resilience in both terrestrial and space-based care environments. This review synthesizes findings from both terrestrial and extraterrestrial environments to evaluate the effectiveness of edible plant-based biophilic interventions. Evidence from clinical studies and long-duration missions suggests that incorporating edible vegetation into confined environments enhances psychological resilience, supports nutritional intake, and contributes to overall well-being. The presence of living plant systems has been shown to reduce stress, enhance mood, and foster a sense of connectedness to nature in contexts where natural stimuli are otherwise absent. Together, these results support the role of edible greens as practical, scalable components for designing sustainable, health-promoting environments in both Earth-based and space-based habitats. We examined the role of biophilic interventions, particularly the incorporation of edible greens, in promoting health within confined environments. Biophilic interventions incorporate natural forms, materials, edible plants, and natural light into architectural designs and indoor settings to enhance both physical and mental well-being (Body and Mind Care). Research in clinical settings and space missions has focused on the outcomes associated with human-plant interactions and the development of bio-regenerative plant modules that support sustainable living. These systems grow plants in controlled environments, enabling food production and the regeneration of essential life-support resources, such as oxygen and clean air. They aim to support crew health through food production, air purification, and psychological benefits, particularly during long-duration missions. We conducted a systematic review, searching databases including PubMed and Scopus, and selected 124 studies based on the PRISMA criteria to analyze the impact of these interventions in eldercare, hospitals, isolation-wards, and spaceflight. Incorporating natural elements into confined habitats yields notable psychological and physiological benefits. In healthcare and indoor environments, the presence of greenery consistently reduces stress, elevates mood, and improves patients’ perception of their surroundings, often contributing to faster recovery. These effects are not limited to hospitals and eldercare settings. In remote and extreme environments, such as polar research stations and space missions, plant interaction can alleviate cognitive fatigue, reduce monotony, and strengthen team cohesion. Integrating edible greens and biophilic elements into confined settings—such as hospitals, eldercare facilities, and space habitats—offers measurable benefits for psychological resilience, reduced physiological stress, and improved cognitive performance. These systems serve dual purposes: therapeutic exposure to nature and support for nutritional or regenerative goals. In hospitals and long-term care, interventions like healing gardens or nature-themed spaces have been shown to reduce anxiety, pain perception, and cortisol levels, while enhancing mood and focus (Beukeboom et.al., 2012; Detweiler et al., 2012). However, high-risk environments like ICUs and operating rooms face practical barriers, including infection control, equipment sensitivity, and space limitations. Similarly, in analog and orbital habitats such as HERA or the ISS, biophilic integration is constrained by power, volume, microbial safety, and crew workload. Despite these constraints, evidence supports the feasibility of modular, low-risk systems—including sealed plant modules, artificial daylighting, and virtual green exposure—tailored to operational demands. As confined living environments become more common across clinical and off-world contexts, biophilic strategies present an adaptable, scalable framework for enhancing well-being, with minimal disruption to safety or efficiency.